Examining the construct validity of the adapted California Critical Thinking Dispositions (CCTDI) among university students in Malaysia - Wan Sulaiman, Wan Shahrazad; Abdul Rahman, Wan Rafaei; Dzulkifli, Mariam Adawiah (Elsevier, 2010)
This research aims at evaluating the psychometric properties of the adapted California Critical Thinking Dispositions (CCTDI) particularly the construct validity. CCTDI consists of 75 Likert-type items measuring seven dispositions, namely truth-seeking, open-mindedness, analyticity, systematicity, inquisitiveness, self-confidence and maturity. The participants of this study involved 425 undergraduate and graduate students. Results showed that the CCTDI has satisfactory construct validity with seven subscales extracted and confirmed by exploratory and confirmatory factor analyses. These evidences of construct validity were further supported with the results of high Cronbach alpha indicating that it is a valid and reliable instrument to measure critical thinking dispositions.